2013
DOI: 10.1155/2013/218970
|View full text |Cite
|
Sign up to set email alerts
|

Repeated Bout Effect Was More Expressed in Young Adult Males Than in Elderly Males and Boys

Abstract: This study investigated possible differences using the same stretch-shortening exercise (SSE) protocol on generally accepted monitoring markers (dependent variables: changes in creatine kinase, muscle soreness, and voluntary and electrically evoked torque) in males across three lifespan stages (childhood versus adulthood versus old age). The protocol consisted of 100 intermittent (30 s interval between jumps) drop jumps to determine the repeated bout effect (RBE) (first and second bouts performed at a 2-week i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
41
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(52 citation statements)
references
References 36 publications
9
41
1
1
Order By: Relevance
“…Some studies found no difference between children and adults [48] and between adolescents and adults [49] during isokinetic contractions. Similar conclusions have also been reported between children and adults during isometric tasks [33,42,[50][51][52]. However, some authors observed higher co-activation levels during submaximal isometric contractions in children compared to adults [44], with a level of antagonist co-activation, which tended to decline between seven and 11 years.…”
Section: Antagonist Co-activationsupporting
confidence: 83%
See 1 more Smart Citation
“…Some studies found no difference between children and adults [48] and between adolescents and adults [49] during isokinetic contractions. Similar conclusions have also been reported between children and adults during isometric tasks [33,42,[50][51][52]. However, some authors observed higher co-activation levels during submaximal isometric contractions in children compared to adults [44], with a level of antagonist co-activation, which tended to decline between seven and 11 years.…”
Section: Antagonist Co-activationsupporting
confidence: 83%
“…According to the Amann and Noakes' theories, this lower peripheral fatigue should result in reduced afferent feedback and therefore a reduced central fatigue in children, if no specific protective mechanism is involved. This is actually what Gorianovas et al [52] reported following a fatiguing plyometric exercise in children compared to adults. However, the same team also observed a greater central fatigue in adolescents compared to adults after a sustained voluntary maximal contraction of the knee extensors [38].…”
Section: Interplay Between Peripheral and Central Factorssupporting
confidence: 70%
“…Several methodological issues could explain the relatively limited number of studies that have compared the effects of ECC and CON exercises: (a) the difficulty in isolating ECC and CON actions during typical everyday movements; (b) the rigorous methodology required to compare ECC and CON exercise in standardized experimental conditions of power output (ie, at the same mechanical power) or oxygen consumption (ie, at the same metabolic rate or oxygen consumption [normalV˙normalO2] level, with mechanical power 3‐5 times higher during ECC cycling); and (c) specific ECC pedal ergometers have only acquired widespread usage in the last decade. However, to date, only a few studies have focused on ECC training in pediatric populations, none of which have tested ECC cycling training. To our knowledge, the impact of ECC cycling training on all aspects of total and segmental body composition has not yet been explored in adult or young obese patients.…”
Section: Introductionmentioning
confidence: 99%
“…That is, the high force and lengthening nature of eccentric actions might cause damage to the muscle. However, it has consistently been reported that bouts of eccentric exercise in youths results in similar, and often attenuated, symptoms of exercise‐induced muscle damage, as compared with adults . When used longitudinally, eccentrically biased training can provide a range of benefits including enhanced concentric and eccentric strength, change of direction ability, sprint and jump performance, and decreased injury incidence .…”
Section: Introductionmentioning
confidence: 99%